Path to Enhanced National Accreditation of Basic Medical Education Programs in Libya - Salem Elfard; Zinab Elfituri; Amal Alshebani (AlQalam Journal of Medical and Applied Sciences, 2024)
As Libya continues to strive for excellence in healthcare, national accreditation plays a pivotal role in shaping the future of medical education and improving patient outcomes. In order to realize this objective, greater collaboration has to be maintained between local medical colleges, the National Center for Quality Assurance and Accreditation of Educational and Training Institutions, and other stakeholders. This study aimed to overcome the challenges and barriers medical colleges face in securing the national accreditation of basic medical education programs offered locally. This study critically reviewed the national accreditation process of basic medical education programs offered in Libya. This includes highlighting any weaknesses or shortcomings in the audit process and suggesting means to improve this process. In terms of the methodology followed, this study was survey-based. The questionnaire consisted of three parts covering different audit process aspects. Several key areas for improvement are highlighted as a result. The data was collected through survey auditors. The data were analyzed using SPSS version 27 and a significance level of p < 0.05 was used. Most of the questionnaire respondents were from the University of Benghazi and the University of Zawia. 57.9% of respondents hold PhD degrees. The majority of respondents (57.9%) disagree or strongly disagree on having enough time to review documents; however, 84.2% strongly agree or agree that team size is appropriate. Over 70% agreed there is vague, unclear language in some indicators, and 94.8% agreed that there are similarities and redundancies between some indicators across standards. On the other hand, 31.6% of auditors cited challenges with standard 7, making it the most problematic. Standards 2 and 9 also posed considerable issues based on facing difficulties for 21.1% of auditors. Standard 2 stands out as lacking alignment between program evidence provisions and indicator requirements according to 63.2% of auditors. Focusing on the audit process in all aspects and correcting any areas of weakness would improve the clarity, uniformity, and fairness of the national accreditation process. بينما تواصل ليبيا سعيها لتحقيق التميز في مجال الرعاية الصحية، يلعب الاعتماد الوطني دورًا محوريًا في تشكيل مستقبل التعليم الطبي وتحسين نتائج المرضى. ومن أجل تحقيق هذا الهدف، لا بد من الحفاظ على تعاون أكبر بين كليات الطب المحلية، والمركز الوطني لضمان الجودة واعتماد المؤسسات التعليمية والتدريبية، وأصحاب المصلحة الآخرين. هدفت هذه الدراسة إلى التغلب على التحديات والعوائق التي تواجهها كليات الطب في تأمين الاعتماد الوطني لبرامج التعليم الطبي الاساسي المقدمة محليا. استعرضت هذه الدراسة عملية الاعتماد الوطني لبرامج التعليم الطبي الاساسي المقدمة في ليبيا. ويتضمن ذلك تسليط الضوء على أي نقاط ضعف أو قصور في عملية التدقيق واقتراح وسائل لتحسين هذه العملية. ومن حيث المنهجية المتبعة، كانت هذه الدراسة قائمة على المسح. حيث كان الاستبيان مكونا من ثلاثة أجزاء تغطي الجوانب المختلفة لعملية التدقيق. ونتيجة لذلك، تم تسليط الضوء على العديد من المجالات الرئيسية للتحسين. تم جمع البيانات وتحليلها باستخدام SPSS الإصدار 27 وتم استخدام مستوى أهمية P <0.05. كان معظم المشاركين في الاستبيان من جامعة بنغازي وجامعة الزاوية. 57.9% من أفراد العينة يحملون درجة الدكتوراه. غالبية المشاركين (57.9%) لا يوافقون أو لا يوافقون بشدة على توفير الوقت الكافي لمراجعة المستندات؛ ومع ذلك، 84.2% يوافقون بشدة أو يوافقون على أن حجم الفريق مناسب. وافق أكثر من 70% على وجود لغة غامضة وغير واضحة في بعض المؤشرات، ووافق 94.8% على وجود أوجه تشابه وتكرار بين بعض المؤشرات عبر المعايير. ومن ناحية أخرى، أشار 31.6% من أعضاء فرق التدقيق إلى تحديات المعيار 7، مما يجعله الأكثر إشكالية. كما طرح المعياران 2 و9 مشكلات كبيرة بناءً على مواجهة الصعوبات بالنسبة لـ 21.1% من المراجعين. يبرز المعيار 2 باعتباره يفتقر إلى التوافق بين ما قدمته البرامج من أدلة ومتطلبات المؤشرات وفقًا لـ 63.2% من المدققين. إن التركيز على عملية التدقيق في جميع الجوانب وتصحيح أي نقاط ضعف من شأنه أن يحسن الوضوح والتوحيد والعدالة في عملية الاعتماد الوطنية